Formulated food inks for extrusion-based 3D printing of personalized foods: a mini review. (April 2022) - Ma, Yizhou; Zhang, Lu
Highlights: Infill density and patterns are critical to control the texture of 3D-printed food. Spatial distributions of ingredients impact flavor perceptions in 3D-printed foods. Longitudinal consumer insights of 3D food printing are needed for future research. Robust 3D printers are needed to produce personalized foods timely and accurately. Abstract : 3D food printing is an emerging technology to structure foods from digital designs. A number of food inks are formulated to 3D/4D print foods with customized appearance. This mini review focuses on the recent developments in 3D printing of personalized foods with modified sensorial properties (e.g. texture and flavor). Varying sensory perceptions of printed food could lead to eating behavior changes among consumers and potentially achieve personalized nutrition. Modifying geometric designs and varying spatial distributions of ingredients are common techniques to alter sensorial properties of printed foods. The high degree of customization of 3D food printing indicates its potential as an on-demand production tool for personalized foods. Nevertheless, we suggest that longitudinal consumer insights and robust printers are needed to further achieve 3D printing of personalized foods.